ChemInform Abstract: Trifluoromethanesulfonic Acid Catalyzed Synergetic Oxidative/[3 + 2] Cyclization of Quinones with Olefins. Issue 9 (4th March 2014) - Meng, Lingkui; Zhang, Guanghui; Liu, Chao; Wu, Kun; Lei, Aiwen
Abstract A synthesis of tetrahydrobenzodifurans and tetrahydrobenzofurans in a TfOH‐catalyzed direct C‐H functionalization of benzoquinone and naphthoquinone with olefins is presented.